2002
DOI: 10.1016/s0378-1135(01)00515-6
|View full text |Cite
|
Sign up to set email alerts
|

Replicon typing of F18 fimbriae encoding plasmids of enterotoxigenic and verotoxigenic Escherichia coli strains from porcine postweaning diarrhoea and oedema disease

Abstract: The presence of ®mbrial adhesin F18 is frequently found in enterotoxigenic Escherichia coli (ETEC) and verotoxigenic E. coli (VTEC) strains responsible for diarrhoea and oedema disease of weaned pigs. The F18 adhesin occurs in two antigenic variants: F18ab is characteristic of VTEC while F18ac is more typical for ETEC. F18 encoding plasmids of 17 phenotypically characterized porcine E. coli isolates (10 ETEC, 6 VTEC and 1 ETEC/VTEC) were tested with a DNA probe for F18 ®mbrial adhesin and with replicon probes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 21 publications
1
20
1
Order By: Relevance
“…Later analysis of pTC found that it contained a putative pathogenicity island (PAI) with a 10-kb fragment containing genes encoding the ST enterotoxins (52). Mainil (51). Those authors also observed that variants of the F18 adhesin exist: F18ab-encoding plasmids, which were highly variable in their sizes within a population examined, and F18ac-encoding plasmids, which were found to be of a more consistent size.…”
Section: Porcine Etec Plasmidsmentioning
confidence: 91%
See 1 more Smart Citation
“…Later analysis of pTC found that it contained a putative pathogenicity island (PAI) with a 10-kb fragment containing genes encoding the ST enterotoxins (52). Mainil (51). Those authors also observed that variants of the F18 adhesin exist: F18ab-encoding plasmids, which were highly variable in their sizes within a population examined, and F18ac-encoding plasmids, which were found to be of a more consistent size.…”
Section: Porcine Etec Plasmidsmentioning
confidence: 91%
“…The work of Couturier et al resulted in the development of an invaluable set of DNA probes specific for each known incompatibility group of the Enterobacteriaceae that allowed screening for replicon-associated regions that were unique to each known plasmid type (34). Based on these probes, others have devised PCR-based replicon typing schemes (25,51,67,89,107,173), which identify the major Inc types occurring among the Enterobacteriaceae. Further refinements of replicon-based plasmid classification are likely, as the influx of genome sequencing data continues to increase and thus clarifies our understanding of plasmid structure and also because novel plasmid groups continue to be identified (186).…”
Section: Plasmid Incompatibility and Classificationmentioning
confidence: 99%
“…This plasmid also contained truncated remnants of an F transfer region and a mosaic of mobile genetic elements, suggesting that it is transfer deficient and might be constantly in flux due to insertion sequence-driven genetic recombination. Previous reports have identified F18 and K88 porcine ETEC virulence plasmids on multiple IncF-type plasmid replicons, suggesting that this particular plasmid may represent only one variant of F18 plasmids circulating among swine ETEC isolates (13,28). UMNF18 contained a second IncFIIA-like plasmid, pUMNF18_IncFV, that was 103 kb (see Fig.…”
Section: Resultsmentioning
confidence: 83%
“…Interestingly, a few Stx-2e toxin genes were present among E. coli isolates from diarrheic piglets without any clinical signs of edema disease. However, since Stx-2e was associated with F18 fimbriae genes, these are variants of F18ac, which are more typical of ETEC responsible for diarrhea in piglets (Fekete et al 2002). In addition, occurrence of Stx-2e toxin genes in conjunction with F18 fimbriae genes indicates that these pathogens persist in porcine population in Zimbabwe despite comparatively low incidence of edema disease in the country (M. Mavenyengwa, University of Zimbabwe, personal communication).…”
Section: Discussionmentioning
confidence: 99%